How to Integrate Culturally Responsive Teaching Approach in Project Based Learning Model in Elementary Schools? - Syawaludin, Ahmad; Andriyanto, Alvin; Maulana, Anggareza; Febriana, Ike Amanda; Fajriyah, Luluk; Fadilla, Salsa Nur (Proceedings Series of Educational Studies, 2024)
This study aims to describe the application of the culturally responsive teaching (CRT) approach integrated into the project based learning (PjBL) model in elementary schools. This study is a qualitative study with a case study type. Data collection techniques were carried out through interviews and document analysis through focus group discussions attended by 15 elementary school teachers in Malang City, East Java. Content analysis was applied in this study to obtain a design for integrating CRT into PjBL in elementary schools applied in Natural and Social Sciences (IPAS) learning. Integration of CRT into PjBL builds more meaningful and relevant student engagement with their cultural background. CRT integrated into the PjBL model not only encourages students to think critically through projects to create products such as infographics, but also allows them to connect scientific concepts with their cultural context and social environment such as surrounding traditions as an effort to protect the environment. Recommendations for the design of a PjBL model integrated with CRT require careful planning to ensure that each stage of learning is not only centered on the project, but also considers the cultural diversity of students.